HUBUNGAN USIA DENGAN KEJADIAN ATONIA UTERI PADA IBU POST PARTUM DI RSUD DR SOEDJONO SELONG KABUPATEN LOMBOK TIMUR NUSA TENGGARA BARAT - Herlinawati Herlinawati; Rachma Meilinda; Adib Ahmad Shammakh; Ida Bagus Yuda Andika (Nusantara Hasana Berdikari, 2022)
Atonia uteri is a state of weak tone or uterine contraction, which causes the uterus to be unable to close open bleeding from the site of placental implantation after the baby and placenta are born. Maternal mortality in Indonesia is still relatively high, one of the causes is postpartum bleeding, especially caused by uteri atonia. This study aims to find out the relationship of age with the incidence of uteri atonia in postpartum mothers in RSUD. Dr. Soedjono Selong NTB. This study is observationally analytical using cross sectional design. The size of the study sample was 206 samples. The sampling technique is purposive sampling. The data was analyzed using the Chi-square test. The results of this study were obtained age with a risk category of 67 (32.5%) and a category of not at risk as much as 139 (67.5%). There was an age relationship with the incidence of uteri atonia in postpartum mothers with a p-value of 0.000. The conclusion in this study was an age-related relationship with the incidence of atonia uteri postpartum mothers in RSUD. Dr. Soedjono Selong NTB.